1992
DOI: 10.1007/bf02047881
|View full text |Cite
|
Sign up to set email alerts
|

Experimental carcinogenesis at sutured and sutureless colonic anastomoses

Abstract: This study explores the role of sutures and the healing colonic wound in experimental carcinogenesis. One hundred sixty rats underwent surgery with colotomy and repair using silk, steel, or Vicryl (Ethicon, Somerville, NJ) sutures or a sutureless technique. Forty rats had a sham procedure. All animals received azoxymethane for 12 weeks at a dose of 10 mg/kg/week. Half the rats commenced carcinogen before surgery, and half commenced it eight weeks after surgery. Animals with anastomotic tumors were found in 46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The present study thus corroborates the findings of McCue et al [3] and O'Donell el al. [4] pointing to the importance of the inter action of sutures with the mucosa in tumour formation, and in addition confirms the role of colonic crypt cell proliferation in carcino genesis.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The present study thus corroborates the findings of McCue et al [3] and O'Donell el al. [4] pointing to the importance of the inter action of sutures with the mucosa in tumour formation, and in addition confirms the role of colonic crypt cell proliferation in carcino genesis.…”
Section: Discussionsupporting
confidence: 83%
“…More and more evidence is now accumu lating that sutures themselves may enhance tumour formation at an anastomosis, over and above that caused by the healing wound itself [3,4], Classical experiments by Pozharisski [23] have shown that the chronic, irri tating effect of suture material caused en hanced tumour formation in the caecum after the administration of dimethylhydrazine, a chemical carcinogen. Calderisi and Freeman [24] implanted various sorts of suture mate rial without creating an actual anastomosis and also noted an enhanced tumour yield at the site at which non-absorbed or slowly ab sorbed suture material had been implanted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] The different characteristics of the suture materials used for colorectal anastomosis may also predispose to local recurrences. 1,11,12 Various methods have been used for restoring continuity after curative resection of colorectal cancers. Examples reported clinically over the last 10 years include the biofragmentable anastomotic ring, 13-17 the AKA2 (and AKA4) compression device, 18,19 and a series of polypropylene buttons 20 as well as the creation of manual anastomosis using different suture materials, and stapled anastomosis.…”
mentioning
confidence: 99%